Dimensioni e caratteristiche della nuova emigrazione italiana - Corrado Bonifazi; Frank Heins; Enrico Tucci (Quaderni di Sociologia, 2021)
The great recession of 2007 to 2013 led to an increase in the number of Italians that emigrated abroad. In general, the population registers only count the movements of individuals who communicate their change of residence. The new longitudinal system for managing the demographic information developed by Istat (the Italian National Institute of Statistics) allows to provide a measure of migratory flows that include a significant part of population register registrations and deregistrations ‘ex officio’ (or, according to the Italian administrative form, ‘for other reasons’). By combining these data on migratory movements and information from other data sources, such as the 2011 population census and the acquisitions of citizenship, it is possible to identify the role of naturalized Italians, to analyse the propensity to emigrate of Italians by sex, generation and educational attainment, as well as to evaluate the territorial dimension of the phenomenon. The emigration of Italians with a university degree is one of the aspects that sparks the greatest interest among the media and migration scholars. In fact, if in absolute value, the contribution of graduates to international migration flows is substantially similar to that of individuals with lower educational qualifications and high school graduates, in terms of propensity the data show higher values for young people with a university degree. The first data on return migration of Italians could indicate both the difficulty of integrating in the countries of arrival and the existence of migratory projects aimed at a short duration. These two different and almost opposite dynamics will be verified subsequently through more in-depth analysis.